2021
DOI: 10.1037/lat0000177
|View full text |Cite
|
Sign up to set email alerts
|

Relations among acculturative stress, internalizing symptoms, and prosocial behaviors in Latinx college students.

Abstract: Acculturative stress is viewed as detrimental to the mental health and prosocial behaviors of Latinx young adults, but empirical research on the topic is scarce. The present study examined the intervening role of internalizing symptoms in associations between acculturative stress and prosocial behaviors in Latinx college students. Participants included 1410 (74.9% women; M age = 19.71 years; 77.5% U.S.-born) Latinx college students, who reported on their levels of acculturative stress, internalizing symptoms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
(114 reference statements)
1
9
0
Order By: Relevance
“…In addition to the immense personal suffering associated with anxiety and depression, experiencing these internalizing problems during young adulthood contributes to various negative outcomes both concurrently and prospectively (Naicker et al, 2013), including lower graduation rates (Breslau et al, 2008) and higher levels of unemployment (Kawakami et al, 2012). For Latino youth, and Mexican-origin youth in particular, dealing with acculturative stress and discrimination can lead to higher rates of anxiety and depression symptoms than youth who are members of other ethnic groups (Bridges et al, 2021; Maiya et al, 2021; Stein et al, 2019; Suarez-Morales & Lopez, 2009; Torres, 2010). Given this widespread public health problem, it is important to identify factors that contribute to anxiety and depression symptoms during young adulthood, which may then highlight potential prevention and intervention targets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the immense personal suffering associated with anxiety and depression, experiencing these internalizing problems during young adulthood contributes to various negative outcomes both concurrently and prospectively (Naicker et al, 2013), including lower graduation rates (Breslau et al, 2008) and higher levels of unemployment (Kawakami et al, 2012). For Latino youth, and Mexican-origin youth in particular, dealing with acculturative stress and discrimination can lead to higher rates of anxiety and depression symptoms than youth who are members of other ethnic groups (Bridges et al, 2021; Maiya et al, 2021; Stein et al, 2019; Suarez-Morales & Lopez, 2009; Torres, 2010). Given this widespread public health problem, it is important to identify factors that contribute to anxiety and depression symptoms during young adulthood, which may then highlight potential prevention and intervention targets.…”
Section: Introductionmentioning
confidence: 99%
“…Third, we examined these associations in a sample of Mexican-origin youth, which contributes to the generalizability of previous work in this area that has focused on predominantly White adolescents. This is especially important given the higher rates of anxiety/depression in ethnic minority youth, which are due, at least in part, to experiences of acculturative stress and discrimination (Bridges et al, 2021; Maiya et al, 2021; Stein et al, 2019; Suarez-Morales & Lopez, 2009; Torres, 2010). Fourth, we used multimethod assessments of temperament (i.e., self- and parent-report), which helps capture temperament constructs more validly and adds to past longitudinal work that relied on only a single assessment method.…”
Section: Introductionmentioning
confidence: 99%
“…(Squid) The minority stress model (Brooks, 1981;Meyer, 2003) describes how LGBTQ+ individuals are at risk for additive stress due to experiences of discrimination, homophobic remarks, concealing, and disclosing their sexual identity. Similar to acculturative stress (e.g., Maiya et al, 2021), the process of navigating sexual identity within highly stressful and unaffirming contexts may particularly affect the mental health of LGBTQ+ emerging adults.…”
Section: Acculturative Stress During Identity Negotiationmentioning
confidence: 99%
“…Although directly supportive evidence on work-related injuries and stress in caregivers and their relations to quality of family relationships and youth prosocial behavior is sparse, there is some supportive evidence on these expected relations in U.S. Latino families and youth. Prior work shows that stress experiences negatively impacted prosocial behaviors in youth [ 28 , 29 , 30 , 31 ]. One recent study also showed that stress is positively related to family conflict and negatively to youth prosocial behaviors [ 32 ].…”
Section: Introductionmentioning
confidence: 99%